Development of a method for studying traffic of multiservice networks - Morkun, Volodymyr Stanislavovych; Hryshchenko, Svitlana Mykolaivna; Nizhehorodtsev, Vladyslav Oleksandrovych; Filonenko, Mykhailo Mykolaiovych; Lahovskyi, Volodymyr Viktorovych (Національний університет "Запорізька політехніка", 2023)
The constant growth in the volume of information, the increase in the speed of information flows in digital communication networks, as before, makes the task of assessing the service stability for traffic flows an urgent one. A simple solution to ensure high service stability is to build a network of sufficient capacity for any traffic that will be thrown at it. To solve the problems of analyzing telecommunication systems, it is necessary to have appropriate models and engineering methods that allow to assess the service stability and predict the characteristics of their operation based on measurement data. In these conditions, the development of new methods for analyzing the traffic of multiservice networks that provide simplicity of calculations and their acceptable accuracy becomes especially relevant.

Постійне зростання обсягу інформації, збільшення швидкості передачі інформаційних потоків у цифрових мережах зв’язку, як і раніше, залишається актуальним завдання оцінки якості обслуговування потоків трафіку. Простим рішенням для забезпечення високої якості обслуговування є побудова мережі достатньої потужності для будь-якого трафіку, який буде кинутий на нього. Для розв’язання проблем аналізу телекомунікаційних систем необхідно мати у своєму розпорядженні відповідні моделі та інженерні методи, що дозволяють на основі даних вимірювань оцінювати якість надання послуг та прогнозувати характеристики їх роботи. У цих умовах розробка нових методів аналізу трафіку мультисервісних мереж, що забезпечують простоту розрахунків та їхню прийнятну точність, стає особливо актуальною.
Keywords: multiservice networks; traffic; quality; faults; method; user; мультисервісні мережі; трафік; якість; несправності; метод; користувач